Measuring the Earth's Synchrotron Emission From Radiation Belts With a Lunar Near Side Radio Array. Issue 2 (8th February 2020) - Hegedus, Alexander; Nénon, Quentin; Brunet, Antoine; Kasper, Justin; Sicard, Angélica; Cecconi, Baptiste; MacDowall, Robert; Baker, Daniel
Abstract: The high kinetic energy electrons that populate the Earth's radiation belts emit synchrotron emissions because of their interaction with the planetary magnetic field. A lunar near side array would be uniquely positioned to image this emission and provide a near real time measure of how the Earth's radiation belts are responding to the current solar input. The Salammbô code is a physical model of the dynamics of the three‐dimensional phase‐space electron densities in the radiation belts, allowing the prediction of 1‐keV to 100‐MeV electron distributions trapped in the belts. This information is put into a synchrotron emission simulator that provides the brightness distribution of the emission up to 1 MHz from a given observation point. Using Digital Elevation Models from Lunar Reconnaissance Orbiter Lunar Orbiter Laser Altimeter data, we select a set of locations near the Lunar sub‐Earth point with minimum elevation variation over various‐sized patches where we simulate radio receivers to create a synthetic aperture. We consider all realistic noise sources in the low‐frequency regime. We then use a custom Common Astronomy Software Applications code to image and process the data from our defined array, using SPICE to align the lunar coordinates with the Earth. We find that for a moderate lunar surface electron density of 250/cm 3, the radiation belts may be detected every 12–24 hr with a 16, 384‐element array over a 100‐km‐diameter circle. Changing electron density can make measurements 10 times faster at lunar night and 10 times slower at lunar noon. Plain Language Summary: The Earth's ionosphere is home to a large population of energetic electrons that live in the balance of many factors including input from the Solar wind and the influence of the Earth's magnetic field. These energetic electrons emit radio waves as they traverse Earth's magnetosphere, leading to short‐lived, strong radio emissions from local regions, as well as persistent weaker emissions that act as a global signature of the population breakdown of all the energetic electrons. Characterizing this weaker emission (synchrotron emission) would lead to a greater understanding of the energetic electron populations on a day‐to‐day level. A radio array on the near side of the Moon would always be facing the Earth and would be well suited for measuring its low‐frequency radio emissions. In this work we simulate such a radio array on the lunar near side, to image this weaker synchrotron emission. The specific geometry and location of the test array were made using the most recent lunar maps made by the Lunar Reconnaissance Orbiter. This array would give us unprecedented day‐to‐day knowledge of the electron environment around our planet, providing reports of Earth's strong and weak radio emissions, giving both local and global information. Key Points: Synchrotron emission between 500 and 1, 000 kHz has a total flux density of 1.4–2 Jy at lunar distances A 10‐km radio array with 16, 000 elements could detect the emission in 12–24 hr with moderate noise Changing electron density can make detections 10 times faster at lunar night and 10 times slower at lunar noon